Electricity Consumption Measurement System Using Current Transformer Sensor TA12-100 - antara, adi surya; Suteja, I Wayan Arsa; Wiantara Putra, I Gede Eka; Putu Widja, Ida Bagus (Program Studi Teknik Elektro Universitas Khairun, 2022)
Electricity consumption measurement system with an embedded system device with Arduino-based technology combined with a current transformer sensor TA12-100 which is connected to the load of electricity consumption. Arduino microcontroller which functions as the main control system that will be connected to the computer, with the aim of future loads so that they can be monitored in real time. By experimenting with the assembly of the Arduino sensor module combined with the current transformer sensor TA12-100, it is continued by comparing the current measurements obtained from the TA12-100 sensor readings to the ampere meter pliers. The results of this study obtained a measurement data for house electrical energy consumption and the percentage error from the comparison of the TA12-100 sensor readings with the readings from the ampere meter measuring instrument. By conducting this research, it is possible to obtain data on what percentage of error is obtained from the use of the TA12-100 sensor, so that later from the experimental results, the TA12-100 sensor is able to properly and correctly monitor electricity consumption at house loads.